Un inedito di Mario Talamanca in tema di homologia kyria (Dike - Rivista di Storia del Diritto Greco ed Ellenistico, 2025)
Abstract: This article presents the unpublished typescript of Mario Talamanca’spaper on homologia kyria, originally delivered at the 1977 Symposion on Greek andHellenistic Law in Chantilly, France, but never included in the published proceedings.The rediscovered text not only fills a nearly fifty-year gap in the historiography but alsoprovides a valuable contribution to one of the most debated issues in the study of Greekprivate law in general and of Attic law in particular. Against the background of theinfluential thesis of H.J. Wolff, which explained the homologia in terms ofZweckverfügung and denied its promissory character, Talamanca advanced a criticalreading of the Attic sources, stressing instead the consensual dimension of homologein.His argumentation – grounded in close philological analysis and in a systematic critiqueof Romanist categories projected onto the Greek experience – shows that the law onhomologia kyria cannot be reduced to a mere procedural mechanism, nor does it admitthe existence of fully consensual contracts in Athens. Rather, Talamanca outlined a thirdway: in Attic law the principle of consensuality had not yet taken hold, but thesignificance of a mere undertaking cannot, in any case, be excluded. The publication ofthis essay, long forgotten and now restored to the scholarly community, seeks not onlyto pay tribute to one of the most original interpreters of Greek legal history in thetwentieth century, but also to reopen the debate on the nature and limits of contractualobligation in the Athenian polis.Riassunto: L’articolo presenta il dattiloscritto della relazione inedita di MarioTalamanca sull’homologia kyria, originariamente pronunciata al Symposion sul dirittogreco ed ellenistico svoltosi a Chantilly, in Francia, nel 1977, ma mai confluita negli attia stampa. Il testo, oggi riscoperto, non solo colma un vuoto quasi cinquantennale nellastoriografia, ma offre anche un contributo prezioso a uno dei temi pi. discussi nellostudio del diritto privato greco in generale e attico in particolare. Sullo sfondo della notatesi di H.J. Wolff, che interpretava l’homologia in base al concetto di Zweckverfügung,negandone il carattere promissorio, Talamanca avanzava una lettura critica delle fontiattiche, ponendone in rilievo la dimensione consensuale. La sua argomentazione –fondata su un’analisi filologica puntuale e su una sistematica critica all’applicazione di2categorie romanistiche alla realt. greca – mostra come la disciplina dell’homologiakyria non possa ridursi a un mero meccanismo processuale, né possa tuttavia condurread ammettere l’esistenza ad Atene di veri e propri contratti consensuali. Talamancadeline. piuttosto una terza via: nel diritto attico non si era ancora affermato il principiodella consensualit., ma la rilevanza del mero impegno non pu. essere in ogni casoesclusa. La pubblicazione di questo saggio, a lungo dimenticato e oggi restituito allacomunit. scientifica, intende non solo rendere omaggio a uno degli interpreti pi.originali della storia giuridica greca nel Novecento, ma anche riaprire il dibattito sullanatura e sui limiti dell’obbligazione contrattuale nella polis ateniese.
Keywords: homologia kyria; Mario Talamanca; Zweckverfügung; consensual contracts; Greek private law